MAKNA SIMBOLIK RITUAL RATIB BERJALAN PADA TRADISI TOLAK BALA: STUDI DESA SUNGAI KURUK III KECAMATAN SERUWAY KABUPATEN ACEH TAMIANG - Arifin, Awaluddin; Subhani, Subhani; Rabiah, Rabiah (Department of Anthropology, 2020)
This research is entitled about the Symbolic Meaning of Ritual Ratib Walking in the Tolak Bala Tradition (Study of Sungai Kuruk III Village, Seruway District, Aceh Tamiang Regency). This research focuses on the process of implementing the walking ratib ritual and the symbolic meaning in the equipment as well as the signs and symbols attached to the walking ratib ritual. Symbolic meanings are the meanings contained in symbols where these symbols have been added to the elements of belief which make the sacred value of a symbol higher. The purpose of this research is to describe the process, the meaning of each symbol and the symbols that exist in the running ritual. This study used a qualitative descriptive approach using symbolic interaction theory. To obtain accurate data and informants, the data collection techniques used were observation, interviews and documentation. The results showed that each symbol in the walking ritual equipment had its own meaning which had been mutually agreed upon so that it could be understood by all of the community.